Pengaruh Tingkat Pendidikan, Usia Dan Tingkat Pendapatan Suami Terhadap Partisipasi Kerja Perempuan Menikah Pada Sektor Industri Pengolahan Di Kabupaten Pelalawan - Rizma, Rizma Olly Via Rhahim; Sari, Lapeti; Utami, Bunga Chintia (Journal of Social and Policy Issues, 2023)
This research is conducted to assess the impact of educational attainment, age, and husband's income on the labor participation of married women in the processing industry sector within Pelalawan Regency. Additionally, the study aims to identify the most influential variable among these factors on the work participation of married women in the same sector and region. The research employed purposive sampling, with a total of 64 respondents, and conducted data analysis using multiple linear regression, assisted by the Eviews 10 software program. The findings indicate that collectively, the level of education, age, and husband's income level have a statistically significant impact on the work participation of married women in the processing industry sector in Pelalawan Regency. On an individual basis, the level of education (X1) exhibits a significant and positive influence on married women's work participation, while age (X2) has a significant and negative effect on their work participation. Similarly, the level of husband's income (X3) significantly and negatively affects the work participation of married women. Among these three independent variables, the level of education emerges as the most dominant factor influencing the work participation of married women in the processing industry sector in Pelalawan Regency. The cumulative effect (R2) of these three variables on the dependent variable accounts for 63%, leaving the remaining 37% influenced by other unexamined variables in this study.